Periosteal Distraction Osteogenesis: An Effective Method for Bone Regeneration. (18th December 2016) - Zhao, Danyang; Wang, Yu; Han, Dong
Abstract : The treatment of bone defects is challenging and controversial. As a new technology, periosteal distraction osteogenesis (PDO) uses the osteogenicity of periosteum, which creates an artificial space between the bone surface and periosteum to generate new bone by gradually expanding the periosteum with no need for corticotomy. Using the newly formed bone of PDO to treat bone defects is effective, which can not only avoid the occurrence of immune-related complications, but also solve the problem of insufficient donor. This review elucidates the availability of PDO in the aspects of mechanisms, devices, strategies, and measures. Moreover, we also focus on the future prospects of PDO and hope that PDO will be applied to the clinical treatment of bone defects in the future.